2023
DOI: 10.1111/nep.14168
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective database analysis of erythropoiesis‐stimulating agent treatment patterns and associated healthcare resource use in patients with non–dialysis‐dependent chronic kidney disease–related anaemia in Japan

Abstract: Aim: This study was conducted to evaluate clinical characteristics, treatment patterns, and healthcare resource use (HCRU) for patients in Japan with non-dialysis-dependent chronic kidney disease (CKD) and anaemia. Methods: This retrospective, longitudinal, epidemiological database extraction study used the JMDC Claims Database, comprising 9.4 million unique beneficiaries. The observation period for anaemia and erythropoiesis-stimulating agent (ESA)/iron treatment was 1 January 2015 to 31 December 2018, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…17 Our findings are also confirmed by a database study using records from the JMDC Claims Database, which reported that only 15% of patients with anemia of NDD-CKD (defined using Japanese Society for Dialysis Therapy guidelines) were treated for anemia. 14 Similarly, a study of records from the Japan Chronic Kidney Disease Database showed that over three-quarters of patients with CKD stages G4 or G5 and Hb level ≤11.0 g/dL were not receiving ESA treatment. 4 However, a paper by Okamoto et al indicates that ESA treatment may differ widely by specialty: 77.3% of patients with anemia of CKD (Hb level ≤11.0 g/dL) and under the care of a nephrologist were prescribed ESAs, but less than one-third of patients with anemia of CKD in other clinical departments were prescribed ESAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Our findings are also confirmed by a database study using records from the JMDC Claims Database, which reported that only 15% of patients with anemia of NDD-CKD (defined using Japanese Society for Dialysis Therapy guidelines) were treated for anemia. 14 Similarly, a study of records from the Japan Chronic Kidney Disease Database showed that over three-quarters of patients with CKD stages G4 or G5 and Hb level ≤11.0 g/dL were not receiving ESA treatment. 4 However, a paper by Okamoto et al indicates that ESA treatment may differ widely by specialty: 77.3% of patients with anemia of CKD (Hb level ≤11.0 g/dL) and under the care of a nephrologist were prescribed ESAs, but less than one-third of patients with anemia of CKD in other clinical departments were prescribed ESAs.…”
Section: Discussionmentioning
confidence: 99%
“…7 , 9 , 13 Currently in Japan, the most commonly used treatments are oral iron therapy in the early stages of CKD and ESAs during the later stages. 14 Intravenous (IV) iron therapy is sparingly used across all CKD stages, and blood transfusion is given mostly to hospitalized patients. 15 However, each of these therapies has its limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Fifth, malnutrition can impact the production and function of red blood cells. 52 Therefore, recognizing and addressing anemia with alacrity is paramount for CKD patients. Treatment options for anemia include EPO replacement therapy, iron supplementation, and red blood cell transfusion.…”
Section: Anemiamentioning
confidence: 99%